Development of Stroke Fast Track Model for Dontan Hospital and Service Network : การพัฒนารูปแบบบริการช่องทางด่วนผู้ป่วยโรคหลอดเลือดสมองโรงพยาบาลดอนตาลและเครือข่ายบริการ - Senamat, Jantajhon (Journal of Nursing and Health Sciences Nakhon Phanom University, 2023)
This research is participatory action research. The objective is to develop a Fast Track service model for stroke patients in Dontan Hospital and service network The sample group consists of 10 nurse in the emergency department, 50 volunteer rescuers, 57 stroke patients, and 70 stroke patient medical records. The study process was composed of 3 phases 1) situation analysis phase 2) Development phase of the stroke fast track model and 3) evaluation phase of the stroke fast track service model Data were collected using patient record forms. Assessment of compliance with guidelines for care and referral of patients by nurses and resuscitation units Test the reliability of the instrument by finding Cronbach’s alpha coefficient, which is equal to 0.75. Data were analyzed using statistics, frequency, percentage, mean and standard deviation, and content analysis. The research results found that Situation analysis phase Service problems were found in both processes and results. Development phase of the stroke fast track service model A comprehensive model for the quality cycle has been developed, which involves 2.1) quick access to fast-track services, 2.2) patient screening, 2.3) patient care processes, 2.4) development of patient care and referral guidelines, and 2.5) Follow up on patients During the evaluation period, it was found that staff were 100% compliant with the stroke fast track service model. Patient results found that patients arrived at the hospital within 120 minutes, the time from the time they had symptoms until they arrived at the hospital. Nurses averaged 75 minutes, initial assessment averaged 4.39 minutes, electrocardiogram averaged 3.67 minutes, preparation for transfer to the host hospital after receiving initial medical treatment averaged within 45 minutes, 100 percent, and from follow-up. After referral, no deceased patients were found. Suggestions: The results of the study indicate that The stroke fast track service model developed helps patients receive care quickly and according to standards and should therefore be used as a service guideline.